A study on ancient casting method via microstructures of impurities and copper found in bronze excavated from the Unified Silla Period (7th to 10th centuries) - Jungeun Choi (Heritage Science, 2023)
Abstract At the Hwangnyongsa temple site, which was founded in 633, at Dongdaebong Mountain in Korea, a large number of gilt-bronze artefacts  have been excavated. Optical microscopy, X-ray fluorescence, scanning electron microscopy, energy dispersive X-ray spectroscopy, focused ion beam and transmission electron microscopy were used to identify the structure of specimen and impurities. This article investigated the impurities and copper grains in bronze Buddha robes from the Hwangnyongsa temple site to determine the ancient bronze craft technology in the  Unified Silla period (seventh–tenth). The XRF results of the specimens indicated that they were made using an alloy of copper and tin, and gold plating was only added on the front side. The microstructure of the specimen was confirmed to be a recrystallized equiaxed hexagonal structure with twins and impurities. The EDS results of the impurities indicated the molar ratio of Cu:S was 2:1, and the electron diffraction pattern substantiated this result  by indicating Cu2S (JCPDF 33-0490). The surface of the specimen consisted of a highlead layer and copper grains. It was hypothesized that the copper grains were formed by the reaction of Pb with the matte (Cu2S) during casting. Lead with black gas would aid in the production of high-quality bronze. The copper grains used were found in Silla, as they have been detected in Koryo bronze artefacts. Hence, it is plausible that the ancient artisans knew that lead provided good bronze quality during the casting process.